2018
DOI: 10.15252/emmm.201708712
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of basic metabolic pathways in microbial sepsis: therapeutic targets at last?

Abstract: Sepsis is a highly lethal and urgent unmet medical need. It is the result of a complex interplay of several pathways, including inflammation, immune activation, hypoxia, and metabolic reprogramming. Specifically, the regulation and the impact of the latter have become better understood in which the highly catabolic status during sepsis and its similarity with starvation responses appear to be essential in the poor prognosis in sepsis. It seems logical that new interventions based on the recognition of new ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
199
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(209 citation statements)
references
References 183 publications
(212 reference statements)
7
199
0
3
Order By: Relevance
“…In fact, the key mediators of this transport (Cpt1a, Cpt2 and Slc25a20) and their master transcriptional regulator (PPARa), are all strongly repressed by infection, in good agreement with recent observations of LPS suppressed program of fatty acid oxidation (Ganeshan et al, 2019) and the requirement of liver PPARa for metabolic adaptation to sepsis (Paumelle et al, 2019). The other signature we found points to a sharp increase in multiple glucocorticoid species ( Figure 3C), suggesting that the infection imposes a strong stress response in the liver, but also to one of the known hallmarks of sepsis pathology: resistance to glucocorticoid treatment (Dendoncker et al, 2019;Van Wyngene et al, 2018). We do find that infection decreases markers of GR activation like the phosphorylation of Ser211 and Ser226 ( Figure 4C).…”
Section: Discussionmentioning
confidence: 52%
“…In fact, the key mediators of this transport (Cpt1a, Cpt2 and Slc25a20) and their master transcriptional regulator (PPARa), are all strongly repressed by infection, in good agreement with recent observations of LPS suppressed program of fatty acid oxidation (Ganeshan et al, 2019) and the requirement of liver PPARa for metabolic adaptation to sepsis (Paumelle et al, 2019). The other signature we found points to a sharp increase in multiple glucocorticoid species ( Figure 3C), suggesting that the infection imposes a strong stress response in the liver, but also to one of the known hallmarks of sepsis pathology: resistance to glucocorticoid treatment (Dendoncker et al, 2019;Van Wyngene et al, 2018). We do find that infection decreases markers of GR activation like the phosphorylation of Ser211 and Ser226 ( Figure 4C).…”
Section: Discussionmentioning
confidence: 52%
“…This glycolytic metabolism of glucose is much less energy efficient, but some cells nevertheless rely predominantly on glycolysis to maintain their ATP pool, even in the presence of oxygen. This phenomenon is termed aerobic glycolysis and is important to provide precursors of essential biosynthesis pathways, such as purine and pyrimidines, amino acids, and triglycerides, which derive from intermediates of glycolysis and the pentose phosphate pathways [58][59][60]. In these cells the pyruvate kinase PKM2 regulates the last step within glycolysis, dephosphorylating phosphoenolpyruvate to pyruvate.…”
Section: Energy Metabolism In the Brainmentioning
confidence: 99%
“…A large proteomic and metabolic screen on plasma of sepsis patients identified that glycolysis, gluconeogenesis, and the citric acid cycle differed prominently between sepsis survivors and nonsurvivors . Levels of lactate, an indicator of cellular and metabolic stress, can be directly correlated with disease severity, morbidity, and mortality in sepsis . In 2017, the World Health Organization (WHO) has recognized sepsis as a global health priority issue.…”
Section: Introductionmentioning
confidence: 99%